Peculiarities of applying reversible hydrogen getters as materials for athodes in gas discharge devices - Borisko, V.N.; Rudaya, I.A.; Sereda, I.N. (Вопросы атомной науки и техники, 2000)
The peculiarities of applying cathodes made of reversible getter hydride-forming alloys in the gasdischarge devices with crossed ExH fields have been revealed. It has been shown that the availability of such electrodes allows to realize a correlation between the intensity of working gas releasing and the discharge parameters. The possibility for controlling erosion processes and heat regimes for the cathode materials has been shown to exist by initiating a controlled hydrogen desorption from the electrodes.